Intranasal Methylprednisolone Ameliorates Neuroinflammation Induced by Chronic Toluene Exposure - Manuel F. Giraldo-Velásquez; Iván N. Pérez-Osorio; Alejandro Espinosa-Cerón; Brandon M. Bárcena; Arturo Calderón-Gallegos; Gladis Fragoso; Mónica Torres-Ramos; Nayeli Páez-Martínez; Edda Sciutto (MDPI AG, 2022)
Inhalants are chemical substances that induce intoxication, and toluene is the main component of them. Increasing evidence indicates that a dependence on inhalants involves a state of chronic stress associated to the activation of immune cells in the central nervous system and release of proinflammatory mediators, especially in some brain areas such as the nucleus accumbens and frontal cortex, where the circuits of pleasure and reward are. In this study, anti-neuroinflammatory treatment based on a single dose of intranasal methylprednisolone was assessed in a murine model of chronic toluene exposure. The levels of proinflammatory mediators, expression levels of Iba-1 and GFAP, and histological changes in the frontal cortex and nucleus accumbens were evaluated after the treatment. The chronic exposure to toluene significantly increased the levels of TNF-α, IL-6, and NO, the expression of GFAP, and induced histological alterations in mouse brains. The treatment with intranasally administered MP significantly reduced the expression of TNF-α and NO and the expression of GFAP (p < 0.05); additionally, it reversed the central histological damage. These results indicate that intranasally administered methylprednisolone could be considered as a treatment to reverse neuroinflammation and histological damages associated with the use of inhalants.